MENINGKATKAN AKTIVITAS DAN KOMPETENSI BELAJAR SISWA MENGGUNAKAN PENDEKATAN KONTEKSTUAL DISERTAI DENGAN LKS PADA MATA PELAJARAN BIOLOGI KELAS VIII4 MTsN BONJOL - Fitri, Arya Wisata; Lufri, Lufri; Noli, Zozy Aneloi (Kolaboratif, 2014)
The approach of this research called classroom action research. The subject of the research were the students of MTsN Bonjol class VIII4. This research aimed to describe the process of improving student learning activities and competencies used a contextual approach which is accompanied by worksheets on subjects MTsN Bonjol VIII4 biology class. This research used a qualitative approach supported quantitative approach. Data were obtained in the form of qualitative and quantitative data. Qualitative data were collected through observation, field notes, and interviews. Quantitative data was obtained through cognitive tests, observation activity, affective and psychomotor competencies. The study findings suggest that the used of contextual approach accompanied worksheets accompanied can improved student learning activities and competencies. The increase was seen in each aspect of the learning activity, affective and psychomotor competencies ranging from pre cycle, the first cycle and second cycle. The increase was also seen in the results of the exam pre cycle is 48, in the first cycle 58.6, and 82.8 in the second cycle. Based on results of research, can concluded the used of contextual approach accompanied worksheets accompanied can improve student learning activities and competencies on subjects MTsN Bonjol VIII4 biology class.